An Analyzing Law Enforcement Challenges in Cross-Border E-Commerce between Indonesia and ASEAN Member States - Yudika Ammara Zulkarnaen (Sidyanusa, 2026)
The rapid growth of cross-border e-commerce within ASEAN has expanded regional trade opportunities while simultaneously generating increasingly complex legal enforcement challenges. Transactions frequently involve multiple jurisdictions, digital platforms, payment intermediaries, and cross-border data flows, creating difficulties in determining applicable law, allocating regulatory responsibility, and enforcing legal remedies. This study examines the principal law enforcement challenges affecting cross-border e-commerce between Indonesia and ASEAN member states through a comparative normative legal analysis. The research analyzes regulatory frameworks governing electronic transactions, consumer protection, and personal data protection across ASEAN jurisdictions, with particular attention to their implications for cross-border enforcement. The findings indicate that despite the widespread recognition of electronic transactions and the existence of supporting legal frameworks across ASEAN, enforcement remains constrained by jurisdictional fragmentation, divergent platform accountability standards, limitations in cross-border evidence gathering, uneven consumer redress mechanisms, and varying approaches to data governance. The study further demonstrates that ASEAN-level instruments have contributed to regulatory cooperation but have not fully resolved practical enforcement barriers. Accordingly, this article proposes several minimum harmonization priorities aimed at strengthening regulatory interoperability, enhancing cross-border cooperation, and improving consumer protection within the ASEAN digital marketplace. The study contributes to the growing discourse on digital trade governance by providing an integrated comparative framework that connects electronic transaction regulation, consumer protection, and data governance within a single enforcement-oriented analysis.